2023
DOI: 10.1038/s41586-023-05963-3
|View full text |Cite
|
Sign up to set email alerts
|

The Smc5/6 complex is a DNA loop-extruding motor

Abstract: Structural maintenance of chromosomes (SMC) protein complexes are essential for the spatial organization of chromosomes1. Whereas cohesin and condensin organize chromosomes by extrusion of DNA loops, the molecular functions of the third eukaryotic SMC complex, Smc5/6, remain largely unknown2. Using single-molecule imaging, we show that Smc5/6 forms DNA loops by extrusion. Upon ATP hydrolysis, Smc5/6 reels DNA symmetrically into loops at a force-dependent rate of one kilobase pair per second. Smc5/6 extrudes lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 37 publications
1
69
1
Order By: Relevance
“…First, we tested whether the purified SMC5/6 used here is able to perform DNA loop extrusion, as reported previously 7 (Figure S2). Indeed, we confirmed that SMC5/6 exhibits loop extrusion of DNA with similar characteristics as reported (Figures S2B-S2E), although we found that yeast SMC5/6 -like human cohesin and yeast condensin -extrudes already as a monomer (Figures S2F-S2I), while Pradhan et al 7 S2G and S2I). While SMC5/6 exhibited dynamics comparable to cohesin, condensin exhibited only brief phases of diffusion (7 ± 4 s, median ± SD) while extrusion phases lasted 13 ± 9 s (median ± SD), and loop slipping was hardly ever observed (1/65 phases; Figure S1J).…”
Section: Phases Of Active Dna Loop Extrusion Are Interspersed By Loop...mentioning
confidence: 93%
See 2 more Smart Citations
“…First, we tested whether the purified SMC5/6 used here is able to perform DNA loop extrusion, as reported previously 7 (Figure S2). Indeed, we confirmed that SMC5/6 exhibits loop extrusion of DNA with similar characteristics as reported (Figures S2B-S2E), although we found that yeast SMC5/6 -like human cohesin and yeast condensin -extrudes already as a monomer (Figures S2F-S2I), while Pradhan et al 7 S2G and S2I). While SMC5/6 exhibited dynamics comparable to cohesin, condensin exhibited only brief phases of diffusion (7 ± 4 s, median ± SD) while extrusion phases lasted 13 ± 9 s (median ± SD), and loop slipping was hardly ever observed (1/65 phases; Figure S1J).…”
Section: Phases Of Active Dna Loop Extrusion Are Interspersed By Loop...mentioning
confidence: 93%
“…S. cerevisiae SMC5/6 was expressed, purified, and fluorescently labelled from S. cerevisiae as described in Pradhan et al (ref. 7 ) with small modifications. The cells were lysed and bound to IgG Sepharose as described in Pradhan et al (ref.…”
Section: Experimental Model and Subject Details Protein Expression An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Smc5/6 also contributes to antiviral immunity (4)(5)(6)(7)(8), though the mechanisms of this activity are not known. For all three eukaryotic SMC complexes, DNA loop extrusion has been directly observed in vitro (9)(10)(11)(12)(13)(14)(15). In prokaryotes, widespread SMC-ScpAB and MukBEF complexes contribute to genome organization and chromosome segregation during cell division (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the role of loop extrusion in DNA immune sensing remains unclear 8,9 . The process of DNA loop extrusion by the eukaryotic SMC complexes has been observed directly by single-molecule experiments in vitro [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%